Effect of Ratio of Soursop and Katuk Leaves with Arabic Gum Concentration on The Quality of Fruit Leather Covered by Chocolate - Siswo Utomo; Herla Rusmarilin; Mimi Nurminah (Jurnal Rekayasa Pangan dan Pertanian, 2014)
The aim of this research was to find the effect of ratio of soursop and katuk leaves pulps with several arabic gum concentration on the quality of fruit leather covered by chocolate. This research was conducted by using completely randomized design with two factors, i.e. :ratio of soursop and katuk leaves pulps (P) : (90% : 10% ; 80% : 20% ; 70% : 30% ; 60% : 40%) and arabic gum concentration (K): (0,5%, 1%, 1,5% and 2%). Parameters analyzed were moisture content, ash content, vitamin C content, curb fiber content, total soluble solid, total acid, proteins content, organoleptic score of colour, taste and texture and organoleptic hedonic values of taste, flavour and texture. The results showed that the ratio soursop and katuk leaves pulps had highly significant effect on moisture content, ash content, vitamin C content, curb fiber content, total soluble solid, total acid, proteins content, score of colour, taste and texture, and hedonic values of taste and texture. Arabic gum concentration had highly significant effect on moisture content, vitamin C content, curb fiber content, total soluble solid, total acid, proteins content, organoleptic score of texture, and hedonic values of texture. Interactions of the two factors had highly significant effect on moisture content, and had no effect on ash content, vitamin C content, curb fiber content, total solubility solid, total acid, proteins content, scores of colour, taste and texture, and hedonic values of  flavor, taste and texture. The ratio of soursop and katuk leaves pulps of (60% : 40%) and Arabic gum concentration of (2%) produced the best quality of fruit leather and more acceptable. Keywords: Arabic gum, fruit leather, katuk leaves, soursop.